Strategi “Islamic Branding” pada Sekolah Islam Terpadu Insantama - Ani Rofiatil Ilmi; Halomoan Harahap (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2025)
This study aims to analyze the implementation of Islamic branding strategies at SIT Insantama in building the institution’s reputation and public trust. Using a qualitative case study method, data were collected through interviews and observations involving school stakeholders. The results reveal that SIT Insantama has successfully positioned itself as a credible Islamic educational institution by integrating Islamic values into all aspects of learning, supported by consistent communication through digital platforms. The branding strategy employed does not merely aim for promotional exposure but serves as a medium of value-based communication and cultural da'wah. The institution prioritizes authenticity, emotional engagement, and alignment with Islamic identity in its communication and branding content. Through selective use of social media trends and a transparent internal communication approach, SIT Insantama builds strong emotional bonds with its stakeholders, enhancing its brand equity in the competitive Islamic education sector. This study offers insights into how value-driven branding can shape institutional identity and contribute to sustainable reputation-building in Islamic educational settings.